Pengaruh Edukasi Gizi Dengan Media Booklet Terhadap Tindakan Pencegahan Anemia Gizi Besi Pada Remaja Putri Di SMPN 4 Tulang Bawang Barat - Desti, Eriska Yudesti; Djamil, Achmad (Jurnal Maternitas Kebidanan, 2024)
Anemia is a condition of the body with lower the normal levels of hemoglobin and erythrocytes. Based on data and information from the Indonesian Ministry of Health, the prevalence of iron nutritional anemia in adolescent girls in Indonesia is 22.7%. The increased incidence of iron nutritional anemia in adolescent girl can also occur due to poor eating habits influenced by low knowledge related to iron nutritional anemia. In this study nutrition education was provided using booklet media, because in this media the target can adjust and learn independently, the material provided is not only in the form of writing but is equipped with color pictures so that it will make young women more interested in reading it. The purpose of this study is to determine the effect of gızı education with booklet media on preventive actions of iron nutrition anemia in adolescent girls at SMPN 4 West Tulang Bawang. The research time began in July-August 2024. The research method is quasy experimental with a two group pretest posttest with control group design. Determination of the number of samples using the Slovin formula and collected by purposive sampling technique resulted in 56 samples. Pretest and Hb level checks were carried out with the help of laboratory medical personnel before the provision of nutrition education and posttest and Hb level checks after nutrition education were carried out once a week for 21 days. In this study using the Mann-Whitney test, the p-value of 0.006 (p <0.05) was obtained, meaning that Ha was accepted, namely there was an effect of nutrition education on the prevention of iron nutrition anemia in adolescent girls at SMPN 4 West Tulang Bawang. The conclusion of this study is that there is an effect of nutrition education using booklet on the prevention of iron nutritional anemia in adolescent girls at SMPN 4 West Tulang Bawang. Suggestions for future researchers to conduct research with a larger population and longer time in order to get maximum results. Keywords: Nutrition Education, Booklet, Anemia Prevention Measures